2006
DOI: 10.1177/0894439305284522
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Questionnaires and the Mode Effect

Abstract: Most methodological evaluations of web-based questionnaires have focused on the issues of sampling and response rates. Some have considered the issues of privacy and ethics. Relatively few have addressed the question of whether people provide different information depending on the mode of questionnaire delivery. This article contributes to this relatively overlooked aspect of the evaluation of web surveys. It presents initial findings from a survey that was designed to enable near-identical groups to respond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…We will return to the anonymity manipulation below. Denscombe (2006) assigned groups of 15-year-old students from the same school to complete either a Web-based or a paper-and-pencil version of a survey of health-related behaviors. There was an unambiguously statistically different pattern of responding on only 1 of 23 questions.…”
Section: Possible Nonequivalence Of Samplesmentioning
confidence: 99%
“…We will return to the anonymity manipulation below. Denscombe (2006) assigned groups of 15-year-old students from the same school to complete either a Web-based or a paper-and-pencil version of a survey of health-related behaviors. There was an unambiguously statistically different pattern of responding on only 1 of 23 questions.…”
Section: Possible Nonequivalence Of Samplesmentioning
confidence: 99%
“…After IRB approval was received, the survey instrument was placed online and the URL link was emailed to individuals who agreed to participate in the study. Research suggests that response rates for paper and web-based surveys are comparable (Kaplowitz et al 2004) and the data produced is generally similar in content, particularly for quantitative items (Denscombe 2006). For open-ended, text-based questions, some evidence suggests that internet surveys may yield longer answers, although further research is needed to confirm this finding (Denscombe 2006).…”
Section: Methodsmentioning
confidence: 99%
“…A series of validation studies in 1998 by Infratest Burke (as reported in Comley, 2002) showed results between the two methods were amazingly close with correlations of results .84 to .95 on all key measures. Denscombe (2006) found that for quantitative data there was little evidence of a mode effect, that is, comparable Web and paper surveys seemed to produce equivalent results.…”
Section: Validitymentioning
confidence: 94%
“…Eysenbach provided a useful checklist for reporting results that addresses these issues. On a strict measure of completion, Denscombe (2006) reported that Web-based questionnaires do slightly better than paper questionnaires (97.1% vs. 81.8%).…”
Section: Response Ratesmentioning
confidence: 99%
See 1 more Smart Citation